2016
DOI: 10.9790/0853-1508063438
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic profile of pesticide poisoning cases admitted in a rural hospital of West Bengal

Abstract: Abstract:Background: In developing countries acute pesticide poisoning remains an important issue and according to WHO (1999)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Among the 375 patients enrolled in our study, the majority were married and only three were divorced. Poisoning was more common among married males than married females, contrary to the findings from most other studies where married female cases outnumbered married male cases .…”
Section: Discussioncontrasting
confidence: 99%
“…Among the 375 patients enrolled in our study, the majority were married and only three were divorced. Poisoning was more common among married males than married females, contrary to the findings from most other studies where married female cases outnumbered married male cases .…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies also show that poisoning are more common in rural areas. 3,8,16,25,26 However, some studies from state of Karnataka, the incidence was more in those who were from urban background. 9,12,24 Majority of the patients in our study belonged to Hindu (91.29%) religion, followed by Muslims (7.39%) and rest 1.32% were Sikhs.…”
Section: Resultsmentioning
confidence: 99%
“…10,23 Other studies also show that most of the patients were Hindus. 7,10,15,23,26,27 Out of 379 patients recruited in the study, majority [235 (62.01%)] were married and rest 144 (37.99%) were unmarried. Consumption of poison was found in higher proportion of married females (65.79%) as compared to married males (59.47%) similar to other studies.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the daily intake of the commonly consumed fruits and vegetables ranged from 26.5% (tangerine) to 40.9% (tomato). Lower values for the daily intake of fruits and vegetables were reported by Sarkar et al (2015) and Agofure et al (2021). Lakshmi (2021) in a study involving adolescent girls in Chennai, India, reported a value of 94.47% for the consumption of vegetables.…”
Section: Discussionmentioning
confidence: 93%